Development of Multimodal Magnetic-Plasmonic Nanocomposites - STAFFORD, SHELLEY MARIA (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2020)
The main aim of this work was to prepare a wide range of magnetic-plasmonic nano- and micro-materials and to explore their properties and potential applications. The combination of both magnetic and plasmonic properties in one nanocomposite is the basis for development of new multifunctional nanomaterials with unique multi-modal properties. These nanocomposites have great potential to find a wide range of applications in nano- and biotechnologies. Chapter 1 of this thesis presents a review of the literature that is of relevance to this research, as well as a discussion on the underlying theory of the work carried out.This includes a discussion on magnetic and plasmonic nanomaterials alongside a broader discussion on magnetism and plasmon resonance, as well as a more general discussion and literature review of current magnetic-plasmonic nanomaterials. Abroad introduction was also given to DNA and calcium carbonate based materials,which are relevant to later chapters in this work.Chapter 2 describes all the details pertaining to the experimental work performed in this thesis, including all the starting materials used and experimental procedures carried out for each chapter. All the instrumental techniques used to characterise the materials prepared in this work were also discussed in detail in this chapter. Chapter 3 focuses on the development of polyelectrolyte-stabilised nanocomposites formed via the electrostatic interactions between PSS-stabilised magnetite of varying concentrations, and PAH-stabilised gold nanoparticles. It details the synthesis and characterisation of three concentrations of PSS-stabilised magnetite nanoparticlesas well as their comprehensive characterisation, as well as the synthesis and characterisation of PAH-stabilised gold nanoparticles. The oppositely charged magnetic and plasmonic nanocomposites were combined to form a hybrid magnetic-plasmonic nanocomposite that retained the gold nanoparticles through multiple magnetic separation cycles. As a proof-of-concept, the study was repeated using unstabilised gold nanoparticles and gold nanoparticles stabilised using acetic acid, and it was found these nanocomposite materials did not retain the gold nanoparticles through magnetic separation. The resulting polyelectrolyte nanocomposites were then tested for their ability to colourimetrically detect mercury ions in aqueous solution. Chapter 4 details the synthesis of anisotropic gold nanoparticles, as well as the preparation of PAH-stabilised magnetite and PAH-stabilised gold nanoparticles forthe development of magnetic and hybrid plasmonic nanostructures using AuAg nanowires. Owing to their monodispersity and reproduciblity, only the two PAH-stabilised nanoparticle species were used in the formation of the AuAg nanowire composite structures. Monitoring of the morphology of these nanocomposite structures over time was carried out using SEM.Chapter 5 presents the development of a one-pot synthetic approach to several concentrations of DNA-stabilised magnetite and DNA-stabilised gold nanoparticles.These nanoparticles were characterised extensively using a variety of instrumentation techniques. These nanoparticles were then combined to form new DNA-stabilised nanocomposites which were analysed using UV-Vis and Raman spectroscopy. Chapter 6 describes the development of magnetic-plasmonic calcium carbonate basedmicromaterials. The synthesis of these materials was achieved through first preparing magnetite nanoparticles stabilised using a variety of different chemical species,as well as preparation of citric acid- and PAH-stabilised gold nanoparticles. The calcium carbonate microstructures were then prepared and the magnetic and/or plasmonic nanoparticles are added to the microstructures by virtue of electrostaticsor layer-by-layer deposition techniques. These nanoparticles were fully characterised by various instrumental techniques.Finally, chapter 7 provides the conclusions of the entire work, and also outlines the main achievements of this body of research. An outline and plan for future work is also presented in this chapter.
APPROVED
Keywords: Nanomaterials; Magnetic; Plasmonic; Chemistry